PENGARUH KEGUNAAN APLIKASI KRETA API INDONESIA DALAM KEHIDUPAN MAHASISWA DI PALEMBANG MENGGUNAKAN METODE REGRESI LINIEAR - Praditya Tama Putra, Ega; Putra Akmal, R. Arfi; Sutabri, Tata (J-ENSITEC, 2024)
This research aims to analyze the influence of the use of the Kreta Api Indonesia Application on the lives of students in Palembang using a simple linear regression method. Data collection was carried out through questionnaires distributed to students who used the application. The independent variable in this research is the usability of the application (Trust/X) and the dependent variable is student participation in using the application (Participation/Y). The results of simple linear regression analysis show that the significance value is 0.006, which is smaller than 0.05. This indicates that the Trust variable (X) has a significant effect on the Participation variable (Y). Apart from that, the calculated t value of 2.861 is greater than the t table of 2.01063, which also confirms that the Trust variable (X) has a significant influence on the Participation variable (Y). From these two test results, it can be concluded that the usability of the Kreta Api Indonesia application has a significant influence on student participation in Palembang in using the application. This shows that the higher the level of student trust in the application, the higher their participation in utilizing the application for their transportation needs.